MOBILE TECHNOLOGIES IN MANAGING EDUCATIONAL PROCESSES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the role and significance of mobile technologies in the educational process. Today, smartphones, tablets, mobile applications, and other modern devices enable learning to be organized in a more interactive, flexible, and personalized manner. Mobile learning not only complements traditional classroom instruction but also expands opportunities for independent learning, distance education, individualized approaches, and constant access to educational resources. The article examines the advantages of these technologies, their areas of application, the challenges they present, and possible solutions. Real-life examples are also used to demonstrate how mobile technologies impact students’ knowledge levels and motivation.